2021
DOI: 10.1002/ueg2.12151
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular invasion quantification could improve risk prediction of lymph node metastases in patients with submucosal (T1b) esophageal adenocarcinoma

Abstract: Aim To quantify lymphovascular invasion (LVI) and to assess the prognostic value in patients with pT1b esophageal adenocarcinoma. Methods In this nationwide, retrospective cohort study, patients were included if they were treated with surgery or endoscopic resection for pT1b esophageal adenocarcinoma. Primary endpoint was the presence of metastases, lymph node metastases, or distant metastases, in surgical resection specimens or during follow‐up. A prediction model to identify risk factors for metastases was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The identification of patients with lymph node metastases is decisive and has therapeutic and prognostic relevance [32] , [33] . RECIST criteria give guidance, but follow-up scans may be necessary for diagnosis, potentially causing delayed detection of nodular spread or recurrence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of patients with lymph node metastases is decisive and has therapeutic and prognostic relevance [32] , [33] . RECIST criteria give guidance, but follow-up scans may be necessary for diagnosis, potentially causing delayed detection of nodular spread or recurrence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] At present, several studies in other solid tumors have confirmed that lymphovascular invasion is closely related to the prognosis of many kinds of malignant tumors such as lung cancer, breast cancer, and esophageal cancer. [7][8][9] However, the relationship between lymphovascular invasion and the prognosis of patients with stage I gastric cancer is still controversial. One view is that lymphovascular invasion is an independent prognostic factor in patients with stage I gastric cancer, [10,11] while the other view is just the opposite.…”
Section: Introductionmentioning
confidence: 99%